Physical therapy exercises for improving intermittent exotropia control post-strabismus surgery: A randomized controlled study - Amany R. Abdel Wahid; Sameh G. Taher; Ayah Mohmoud Mohamed; Doaa Atef (World Scientific Publishing, 2024)
Background: Exotropia control is deteriorated by post-strabismus surgery in many cases. Improving this control is considered as an important factor for success of the strabismus surgery like ocular motor alignment. Objective: To determine the therapeutic effect of postoperative eye exercises on exodeviation eye control after the strabismus surgery. Methods: Forty patients suffering from intermittent exotropia after strabismus surgery were randomly divided into experimental group and control groups. Both groups received the usual medical care, while the experimental group received different types of eye exercises using physiotherapy modalities in 24 sessions over three months (two sessions a week). The measurement of exotropia control for near target and far target using the office-based scale was done before and after the treatment. Results: There was a significant improvement in near eye control post-treatment ([Formula: see text]) in the experimental group compared with control group ([Formula: see text]) as the mean difference was −3.20 and 95% CI of the difference between them was −3.645-−2.755 with [Formula: see text]. Also, far eye control improved post-treatment in the experimental group ([Formula: see text]) compared with control group ([Formula: see text]) with mean difference of −3.250 and 95% CI of the difference between them was −3.727-−2.773 with [Formula: see text]. Conclusions: For patients with intermittent exotropia who had undergone strabismus surgery, the addition of physiotherapy exercises for the eye provided significant improvements in exotropia control for near target and far target.